Review of the Ijārah al-A‘māl Contract on Risk Management of the Employment Relationship between Guides and Rafting Owners in Central Aceh - Wahyuni, Tika; Abubakar, Ali; Eriyanti, Nahara (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study analyzes risk management in the employment relationship between rafting guides and owners in Central Aceh Regency from the perspective of the ijārāh al-a'māl contract in Islamic jurisprudence (fiqh mu'āmalah). The background stems from a series of rafting accidents in Bengkulu and Central Aceh in 2024, resulting in fatalities due to inadequate risk management, such as extreme fatigue and river collisions. The objectives are to evaluate risk management practices, their alignment with Shariah principles, and propose an ideal model based on ijārāh to ensure justice and safety. The method employed is descriptive qualitative with an empirical juridical approach through a case study at sites like the Peusangan and Lukup Badak Rivers. Data were collected via observation, interviews with owners and guides, and documentation. Data analysis involved reduction, presentation, and verification. Findings reveal that employment is formalized through cooperative contracts, trip-based wages (Rp80,000/trip), and protection via BPJS Employment Insurance, aligning with ijārāh al-a'māl principles such as clear wages (al-ujrah al-ma'lūmah) and risk sharing. Risk management strategies include preventive (routine training), curative (medical handling), and distributive (shared responsibilities). However, challenges include limited Shariah understanding, suboptimal protection for minor risks, and wage dependency on weather and tourist numbers. In conclusion, practices lean toward Shariah compliance but require strengthened preventive risk management based on maqāṣid al-sharī'ah for justice, life preservation (ḥifẓ al-nafs), and business sustainability. Recommendations include Shariah training and stable wage schemes.